Biomechanical performance analysis in athletics at the collegiate level - Adeniji, O. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to serve as the platform in presenting biomechanical performance analysis in Athletics at the collegiate level. An inter-collegiate comparison was done to draw upon kinematic data and the role it plays on performance variability. The male 100-meter finalists (n=16) from the 2017 and 2018 Division I Outdoor Track & Field Championships (collegiate experience 3.38 ± 0.60 years) were analysed. Finalists were assigned to one of two groups, Top 3 (n=6) and Rest-of-Field (n=10) based on their placement at these championships. Highlighted was the mean velocity difference (0.30 m/s) and large effect size (0.88) between the two groups from 30-60m. The variable magnitudes reflected differences in technique and an application of sprint mechanics. Therefore, it is appropriate to further investigate the determinant characteristics of college performances.